Estimating dynamic income responses to tax reforms: Swedish evidence - Bertil Holmlund; Martin Söderström (Institute for Labour Market Policy Evaluation (IFAU), 2008)
We study income responses to income tax changes by using a large panel of Swedish tax payers over the period 1991-2002. Changes in statutory tax rates as well as dis-cretionary changes in tax bracket thresholds provide exogenous variations in tax rates that can be used to identify income responses. We estimate dynamic income models which allow us to distinguish between short-run and long-run effects in a straight-forward fashion. For men, the estimates of the long-run elasticity of income with respect to the net-of-tax rate hover in a range between 0.10 and 0.30. The estimates for women are imprecise and statistically insignificant. We simulate the fiscal consequences of a tax reform that reduces the top marginal tax rate by five percentage points. Such a reform may have negligible effects on tax revenues even for relatively small elasticities when the interactions between income taxes and other taxes are taken into account.
Keywords: H24; H31; J22; 330; marginal tax rates; progressive taxes; earned income; tax reform; Steuerreform; Einkommensteuer; Einkommenselastizität; Grenzsteuersatz; Steuerprogression; Schätzung; Schweden